A Partitioned Library: Changing Collecting Priorities and Imagined Futures in a Divided Urdu Library, 1947–49. Issue 3 (3rd May 2020) - Amstutz, Andrew
Abstract: This article argues that the history of a damaged Urdu library in Delhi reveals new perspectives on the ways in which prominent Indian Muslim scholars dealt with the violent displacements of the 1947 Partition of British India and imagined new futures for the Urdu language across the borders of India and Pakistan. The library of the Anjuman-e Taraqqi-e Urdu (Association for the Advancement of Urdu), an influential Urdu literary association, was damaged during the violence following Partition in August 1947. In contrast to the relative absence of official commemorations of Partition in post-colonial South Asia, the Anjuman's leaders documented and publicised the violence of Partition on their library. Moreover, these Urdu scholars used the material process of restoring the damaged library in 1947 and 1948 to rethink the role of the library as a repository to preserve evidence of the continuing production of Urdu knowledge in India. In turn, the disputed division of the library in 1949 illuminates competing visions for Urdu's future in India, Pakistan, and beyond. This story of one Urdu library demonstrates how changing library collecting priorities and material practices shaped broader debates over Urdu's place in twentieth-century South Asia.